The genius of democracy : fictions of gender and citizenship in the United States, 1860-1945 - Olwell, Victoria (University of Pennsylvania Press, 2011)
Victoria Olwell shows how American fiction helped to catalyze democratic models of female genius, especially in the work of such authors as Louisa May Alcott, Henry James, Mary Hunter Austin, Jessie Fauset, and Gertrude Stein.